2018
DOI: 10.1212/wnl.0000000000006050
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of functional abilities in infants, children, and adults with type 1 SMA

Abstract: Our findings confirm that, after the age of 2 years, patients with type 1 spinal muscular atrophy generally survive only if they have gastrostomy and tracheostomy or noninvasive ventilation >16 hours and have low scores on the functional scales. More variability, however, can be expected in those with the mildest phenotype, who achieve head control. These data provide important baseline information at the time treatments are becoming available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 22 publications
4
33
1
Order By: Relevance
“…A recent natural history study reported that only 50% of untreated infants with SMA1 with two copies of SMN2 reached a median age of eight months free of permanent ventilation. 4 In contrast to natural history, in which no patient achieved a CHOP-INTEND score above 40, 15 11 of 12 patients in this study achieved and maintained a CHOP-INTEND score of 40. Patients in the Early Dosing/Low Motor group had rapid mean increases in CHOP-INTEND of 13.7 and 22.0 points at one and three months, respectively.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…A recent natural history study reported that only 50% of untreated infants with SMA1 with two copies of SMN2 reached a median age of eight months free of permanent ventilation. 4 In contrast to natural history, in which no patient achieved a CHOP-INTEND score above 40, 15 11 of 12 patients in this study achieved and maintained a CHOP-INTEND score of 40. Patients in the Early Dosing/Low Motor group had rapid mean increases in CHOP-INTEND of 13.7 and 22.0 points at one and three months, respectively.…”
Section: Discussioncontrasting
confidence: 70%
“…14 Efficacy in motor function is further validated when compared with the poor outcomes associated with severe variants of SMA1 (mean CHOP-INTEND scores of 4.1 to 5.4 and death by age 14 months). 15 These results show the efficacy of using AVXS-101 and support identifying infants via newborn screening to maximize the therapeutic benefit of early treatment, as recently recommended by a panel of SMA experts. 17 The findings also indicate that gene transfer with AVXS-101 is highly relevant and effective for patients with early onset and low CHOP-INTEND scores.…”
Section: Discussionsupporting
confidence: 59%
“…In our study the SATR test revealed that chest deformities in SMA patients occurred more often and were significantly severe than in the healthy individuals. The highest values of SATR were noted in individuals with SMA I and SMA II who most often experienced breathing difficulties and need non-invasive ventilatory support [ 32 34 ]. In the case of patients with SMA III, the test revealed significantly lower values of chest deformities compared to SMA I and SMA II participants.…”
Section: Discussionmentioning
confidence: 99%
“…It is an autosomal recessive neuromuscular disease (NMD) caused by a homozygous deletion or mutation of the survival motor neuron 1 (SMN1) gene on chromosome 5q13, characterized by progressive muscle wasting and debilitating weakness [3][4][5][6][7]. The disease has been classified into subtypes based upon age of onset and motor function achieved [4,[8][9][10]. Type I has onset in infancy and is the most severe and common subtype (representing 50-60% of diagnoses), whereas types II, III, and IV represent later onset, milder phenotypes [4,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The disease has been classified into subtypes based upon age of onset and motor function achieved [4,[8][9][10]. Type I has onset in infancy and is the most severe and common subtype (representing 50-60% of diagnoses), whereas types II, III, and IV represent later onset, milder phenotypes [4,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%